Reportage : a retrospective 1999-2009 - Vicario, Jacqui; Dupont, Stephen, 1967-; National Art School (Australia) (Bondi Junction, N.S.W. : Reportage, 2010)
Reportage : A Retrospective 1999 - 2009, brings together 80 of the most memorable photographs from ten years of the Reportage Festival in a large outdoor exhibition shown at the National Art School in East Sydney, 5 - 21 November 2010. This free public exhibition is curated by festival founders Stephen Dupont, Michael Amendolia, Jack Picone and David Dare Parker with festival director Jacqui Vicario.
Keywords: National Art School (Australia) -- Exhibitions; Documentary photography -- Australia -- Exhibitions; Australian